SARS-CoV-2 viral clearance and viral load kinetics in young children (1-6 years) compared to adults: Results of a longitudinal study in Germany - Anna Sandoni; Angelika Schaffrath Rosario; Janine Michel; Tim Kuttig; Juliane Wurm; Stefan Damerow; Helena Iwanowski; Bianca Finkel; Livia Schrick; Udo Buchholz; Walter Haas; Gianni Varnaccia; et al. (Frontiers Media S.A., 2022)
ObjectiveTo investigate SARS-COV-2 viral clearance and viral load kinetics in the course of infection in children aged 1-6 years in comparison with adults.MethodsProspective cohort study of infected daycare children and staff and their close contacts in households from 11/2020 to 06/2021. Adult participants took upper respiratory tract specimen from themselves and/or their children, for PCR tests on SARS-CoV-2. Data on symptoms and exposure were used to determine the date of probable infection for each participant. We determined (a) viral clearance, and (b) viral load dynamics over time. Samples were taken from day 4-6 to day 16-18 after diagnosis of the index case in the respective daycare group (5 samples per participant).ResultsWe included 40 children (1-6 years) and 67 adults (18-77 years) with SARS-CoV-2 infection. Samples were available at a mean of 4.3 points of time per participant. Among the participants, the 12-day study period fell in different periods within the individual course of infection, ranging from day 5-17 to day 15-26 after assumed infection.Children reached viral clearance at a median of 20 days after assumed infection (95% CI 17-21 days, Kaplan-Meier Analysis), adults at 23 days (95% CI 20-25 days, difference not significant). In both children and adults, viral load decreased over time with trajectories of the mean viral load not being statistically different between groups. Kaplan-Meier calculations show that from day 15 (95% CI 13-15), 50% of all participants had a viral load <1 million copies/ml, i.e. were no longer infectious or negative.ConclusionChildren aged 1-6 and adults infected with SARS-CoV-2 (wild type and Alpha variant) did not differ significantly in terms of viral load kinetics and time needed to clear the virus. Therefore, containment measures are important also in the daycare settings as long as the pandemic continues.